African Travel Writing and Memories of Slavery in Dionne Brand and Saidiya Hartmann (Anclajes, 2022)
The books A Map to the Door of No Return. Notes to Belonging (2001) by Trinidadian-Canadian writer Dionne Brand and Lose your Mother. A Journey Along the Atlantic Slave Route (2006) by U.S. American Saidiya Hartmann address the subject of the journey to Africa, in particular to the symbolic space of the "Door of No Return". We argue that these books contribute to the renewal of the travel writing genre by assembling geographical displacement as ways of reshaping genealogical memories of slavery. In these texts, we find female Afrodiasporic subjects transiting contemporary migration movements and the slave trade routes, accompanied in these experiences by the interrogation of silenced family and collective memories. In this itinerary, the books question and subvert the archives on imperial journeys, while generating new cartographies and reconstructing genealogies organized largely around the experiences of racialized women.
Keywords: Saidiya Hartmann; Dionne Brand; Postcolonial Travel; Afro-descendent Diaspora; Door of No Return